DC Magnetron Deposition And Charaterization of Iron-Platinum Magnetic Thin Films - Low, Pei Ling (2010)
In this research, FePt thin films have been fabricated and characterized to investigate the substrate effects on the structural properties and surface morphologies of the FePt films, and also the thickness effects on the structural and magnetic properties of the films.